Pengaruh Penerimaan Pajak, Penanaman Modal Asing Dan Penananaman Dalam Negeri Terhadap Pertumbuhan Ekonomi Di Indonesia - Rizkika Ananda Agustina; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
According to the Indonesian Statistics Agency (BPS), economic growth in 2023 is estimated to remain strong in the range of 5.05% (yoy), this economic growth is better compared to the last two years considering that the government continues to optimize the recovery period from Covid-19. According to Sadono Sukirno (in Puspitasari et al., 2024) one of the policies to accelerate the development process is to increase government savings, the savings rate Economic growth can be interpreted as a process of increasing the value of output per capita in the long term. The purpose of this study is to determine the effect of Tax Revenue, Foreign Investment (PMA), Domestic Investment (PMDN) on economic growth in Indonesia. This study uses a quantitative approach using time series data sourced from the Central Statistics Agency of Indonesia (BPS) for 2014-2023. The data analysis technique uses multiple regression analysis using the E-views 10 program. The results of the study determine that tax revenue has a significant effect on economic growth in Indonesia, foreign capital revenue (PMA) has a negative and insignificant effect on economic growth, while domestic capital revenue (PMDN) has a positive and significant effect on economic growth.